The Pre-designed Lesson: Teaching with Transdisciplinary Pedagogical Templates (Tpts) - Dobozy, Eva (Technology, knowledge and learning, 2017)
An ongoing challenge in higher education is the support of educators in their development of effective pedagogies. The field of educational research and practice referred to as Learning Design may be able to help educators with no or limited pedagogical training deliver highly interactive and contemporary teaching and learning offerings. The present study reported the findings from a trial of new technologically supported Learning Designs. These pre-designed lessons are referred to as Transdisciplinary Pedagogical Templates (TPTs). These templates contain prepopulated pedagogical instructions to educators and students, but are free of subject specific content allowing them to be used in discipline areas as diverse as teacher education, accounting, engineering or medicine. These TPTs have been designed to assist educators provide constructivist learning experiences, without the need for pedagogical upskilling. This research explored the practical efficacy of the de Bono LAMS template model, documenting educator and student engagement patterns and issues arising from the trial of the five de Bono LAMS sequences. The findings suggest an interest in TPTs by educators and students, but also a reluctance to engage with research, citing mainly a lack of time. The findings also point to a need to better understand students’ affective states and the role of emotional intelligence in technology enhanced learning and teaching provision.